Recent Developments and Applications of Hemicellulose From Wheat Straw: A Review - Huang, Ling-Zhi; Ma, Ming-Guo; Ji, Xing-Xiang; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2021)
Hemicellulose is an important component of plant cell walls, which is mainly used in biofuels and bioproducts. The hemicellulose extracted from different plant sources and plant locations has different microstructure and molecule. Wheat straw is an important biomass raw material for the extraction of hemicellulose. The aims of this review are to summary the recent developments and various applications of hemicellulose from wheat straw. The microstructure and molecule of hemicellulose extracted by different methods are comparably discussed. The hemicellulose-based derivatives and composites are also reviewed. Special attention was paid to the applications of hemicellulose such as biofuel production, packaging field, and adsorbent. The problems and developing direction were given based on our knowledge. We expect that this review will put forward to the development and high-value applications of hemicellulose from wheat straw.